TraR directly regulates transcription initiation by mimicking the combined effects of the global regulators DksA and ppGpp - Gopalkrishnan, Saumya (Proc Natl Acad Sci U S A, 2017)
The Escherichia coli F element-encoded protein TraR is a distant homolog of the chromosome-encoded transcription factor DksA. Here we address the mechanism by which TraR acts as a global regulator, inhibiting some promoters and activating others. We show that TraR regulates transcription directly in vitro by binding to the secondary channel of RNA polymerase (RNAP) using interactions similar, but not identical, to those of DksA. Even though it binds to RNAP with only slightly higher affinity than DksA and is only half the size of DksA, TraR by itself inhibits transcription as strongly as DksA and ppGpp combined and much more than DksA alone. Furthermore, unlike DksA, TraR activates transcription even in the absence of ppGpp. TraR lacks the residues that interact with ppGpp in DksA, and TraR binding to RNAP uses the residues in the β′ rim helices that contribute to the ppGpp binding site in the DksA–ppGpp–RNAP complex. Thus, unlike DksA, TraR does not bind ppGpp. We propose a model in which TraR mimics the effects of DksA and ppGpp together by binding directly to the region of the RNAP secondary channel that otherwise binds ppGpp, and its N-terminal region, like the coiled-coil tip of DksA, engages the active-site region of the enzyme and affects transcription allosterically. These data provide insights into the function not only of TraR but also of an evolutionarily widespread and diverse family of TraR-like proteins encoded by bacteria, as well as bacteriophages and other extrachromosomal elements.